2013
DOI: 10.1242/jeb.087650
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific divergence for adaptations to dehydration stress in Drosophila kikkawai

Abstract: SUMMARYSeveral studies on diverse Drosophila species have reported higher desiccation resistance of females, but the physiological basis of such sex-specific differences has received less attention. We tested whether sex-specific differences in cuticular traits (melanic females and non-melanic males) of Drosophila kikkawai correspond with divergence in their water balance mechanisms. Our results are interesting in several respects. First, positive clinal variation in desiccation resistance was correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
(63 reference statements)
2
12
0
Order By: Relevance
“…The observed effects of physiological acclimation to both high-and low-temperature conditions on stress tolerance are consistent with temperature being a major factor in modulating subsequent performance and fitness in D. melanogaster (e.g., Cossins et al 2002;Kristensen et al 2003;Hoffmann et al 2005a Parkash and Ranga 2013). Similarly, exposure to distinct, seasonal photoperiods had predictable effects on multiple aspects of stress tolerance.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The observed effects of physiological acclimation to both high-and low-temperature conditions on stress tolerance are consistent with temperature being a major factor in modulating subsequent performance and fitness in D. melanogaster (e.g., Cossins et al 2002;Kristensen et al 2003;Hoffmann et al 2005a Parkash and Ranga 2013). Similarly, exposure to distinct, seasonal photoperiods had predictable effects on multiple aspects of stress tolerance.…”
Section: Discussionsupporting
confidence: 69%
“…; Kristensen et al. ; Sisodia and Singh ; Parkash and Ranga ). Similarly, exposure to distinct, seasonal photoperiods had predictable effects on multiple aspects of stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Such a response has not been documented across a wide variety of insect groups, except for several species of Drosophila, and even here variation is typically among early and late life and also among species and sex (e.g. Matzkin et al, 2007;Shahrestani et al, 2012;Parkash and Ranga, 2013;Aggarwal, 2014). Mechanisms that might underlie a decline in tolerance with age are thought to include changes in WLR, probably a function of variation in cuticular hydrocarbon content and composition, melanization, differences in initial body water content and tolerance of dehydration (Nghiem et al, 2000;Gibbs and Markow, 2001;Benoit and Denlinger, 2007;Weldon et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…First, cuticular WLR, which generally dominates loss (Chown et al, 2011), differs among the sexes, as confirmed by pronounced effect size differences between males and females for the influence of WLR on survival. In turn, these differences are likely to be a consequence of variation in cuticle lipid content and/or composition, or cuticle thickness (Parkash and Ranga, 2013;Parkash and Ranga, 2014). Although some evidence exists for thicker cuticles in female mosquitoes (Wood et al, 2010), it seems likely that variation in cuticular lipid amount and composition is more likely to account for variation in WLR (Reidenbach et al, 2014).…”
Section: Research Articlementioning
confidence: 99%
“…While 2La inverted homokaryotypes boosted their mass-specific glycogen content and reduced lipid stores, the converse was true for 2L+ a homokaryotypes [17]. It is noteworthy that increased storage of glycogen, utilized by Drosophila under desiccation stress [29], has been associated with higher dehydration tolerance in flies [29-31], consistent with its proposed role as an osmolyte for water retention [30]. Taken together, these data suggest that genes inside the 2La inversion influence water balance and desiccation resistance, but also that resistance to desiccation is a complex trait, whose precise physiological basis and causal genes remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%